2002
DOI: 10.1021/bm020018x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Preliminary Biological Study of Glycoconjugates of Poly(styrene-co-maleic acid)

Abstract: Three derivatives of the biocompatible polymer poly(styrene-co-maleic anhydride) (SMA) were obtained with 1-amino-1-deoxy-beta-D-galactose, 1-amino-1-deoxy-beta-D-glucose, and 1-amino-1-deoxy-beta-D-lactose, respectively. The amino sugars were chemically conjugated via formation of an amide bond between the anomeric amino group of the sugar residue and the anhydride of the copolymer, giving the corresponding glycoconjugate derivatives. Colorimetric assay of the unreacted amino groups and elemental analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 17 publications
2
40
0
1
Order By: Relevance
“…A particularly interesting case is the copolymerization of maleic anhydride with MVI, which results in alternating copolymers with two chemical handles for further modification (1 in Scheme 3). [17] Amines have been reported to react with anhydride groups of poly(styrene-co-maleic anhydride) up to near quantitative conversion in mixed DMSO/0.5 m NaHCO 3 buffer in 3 h. [79] Isocyanates can react with both alcohols and amines, but under very different conditions. Primary and secondary amines react with polymeric isocyanates quantitatively in a few minutes at 60 8C under stoichiometric conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly interesting case is the copolymerization of maleic anhydride with MVI, which results in alternating copolymers with two chemical handles for further modification (1 in Scheme 3). [17] Amines have been reported to react with anhydride groups of poly(styrene-co-maleic anhydride) up to near quantitative conversion in mixed DMSO/0.5 m NaHCO 3 buffer in 3 h. [79] Isocyanates can react with both alcohols and amines, but under very different conditions. Primary and secondary amines react with polymeric isocyanates quantitatively in a few minutes at 60 8C under stoichiometric conditions.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 In addition, the SMA will probably not affect antibacterial tests due to its high biocompatibility and weak bactericidal effect. 16,26 The SMA-AgNPs, designated AgNPs in the following text and graphs, were prepared chemically by reducing Ag nitrate with NaBH 4 into NPs ( Figure 1C). The particle size was estimated to be 8.6 ± 0.2 nm ( Figure 1G), similar to the AgNP size of AgNP/NSP.…”
Section: Characterization Of the Nsp Agnp/nsp And Agnpsmentioning
confidence: 99%
“…Gal-APP-PAEMA-PCL, bearing hepatic targeting moieties, exhibits the highest phototoxicity for HepG2 cells. It was reported that asialoglycoprotein (ASGP) receptors were expressed plentifully on the surface of hepatoma cells (20,21), and targeting could be accomplished through introduction of galactose residues, such as terminal β-D-galactose and N-acetylgalactosamine residues, which could bind specifically to the ASGP receptors. In our study, the internalization of Gal-APP-PAEMA-PCL for HepG2 cells is higher compared with the polymers without targeting groups.…”
Section: Dark Toxicity and Phototoxicity Of Polymersmentioning
confidence: 99%
“…It was reported that Electronic supplementary material The online version of this article (doi:10.1007/s11095-009-9998-8) contains supplementary material, which is available to authorized users. asialoglycoprotein (ASGP) receptors were expressed plentifully on the surface of hepatoma cells and mammalian hepatocytes, and targeting could be accomplished through introduction of galactose residues, which can bind specifically to the ASGP receptors on the cells (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%